Benjamin Franklin [videorecording (DVD)] - Duncan, Dayton; Mellish, Craig; Squires, Buddy; Coyote, Peter; Duncan, Will; Cieri, David (PBS, 2022)
Ken Burns's two-part, four-hour documentary explores the revolutionary life of one of the 18th century's most complex and consequential figures, whose work and words unlocked the mystery of electricity and helped create the United States.